Biologic Strategies to Improve Nerve Regeneration after Peripheral Nerve Repair - Fowler, John R.; Lavasani, Mitra; Huard, Johnny; Goitz, Robert J. (Journal of Reconstructive Microsurgery, 2015)
Background Peripheral nerve injuries remain a challenging problem for microsurgeons. Direct repair is the gold standard, but often the surgeon is left with a gap that prevents tension-free repair. The use of empty tubes/conduits/allograft has resulted in regeneration of some sensory and motor function, but the results remain suboptimal compared with autograft. However, the use of nerve autograft has associated donor site morbidity and limited availability.Methods A review of the literature was performed to determine current biologic strategies to improve nerve regeneration after nerve repair.Results Nerve conduits, various neurotrophic factors, and stem cells are currently being studied as alternatives to the use of nerve autograft. Conclusions Sensory and motor recovery after peripheral nerve regeneration remains suboptimal, especially in cases where primary nerve repair is not possible. Current strategies to augment nerve regeneration have focused on modulating the presence and activity of Schwann cells, either through direct implantation or by stimulating stem cells to differentiate toward Schwann cells, and through the use of neurotrophic factors to enhance the speed and quality of axon growth. Clinical studies will be necessary to determine the benefit of these strategies.
Keywords: Schwann cells; stem cells; nerve repair